An integrated fault estimation and fault tolerant control method using H∞‐based adaptive observers. (7th August 2020) - Fazeli, S. Mahdi; Abedi, Mostafa
Summary: An integrated fault estimation/fault‐tolerant control (FTC) scheme is developed in this article for nonlinear Lipschitz systems in the presence of external disturbances and actuator failures. To address this problem, coupled uncertainties between the observer error dynamics and the control system are considered, which is conveniently ignored in control approaches based on the separation principle. An H ∞ ‐based adaptive observer is proposed to simultaneously estimate the system states and actuator faults without the restrictive strictly positive realness or persistent excitation conditions. The FTC is constructed by sliding mode control using the estimated states generated by the developed observer. A novel sufficient condition is derived in terms of linear matrix inequality (LMI) including both the system control dynamics and the estimation errors; then, the control parameters and observer gains are simultaneously obtained via solving the mentioned LMI based on the H ∞ optimization. Finally, a flexible joint robot is considered to illustrate the effectiveness of the developed method.